PENGARUH LAMA FERMENTASI TERHADAP MUTU TEPUNG UBI JALAR (Ipomea batatas L.) BERBAGAI WARNA UMBI - Dewi Novita Sari; Rakhmiati Rakhmiati; Etik Puji Handayani (Jurnal WACANA PERTANIAN, 2019)
The usage development can be increased by applying right cultivating and processing  technology to grow sweet potato agroindustry that can help increasing economy value and lengthening storability. One of sweet potato potencies that can be developed in food diversification is sweet potato flour processing. The objective of this research is to study about the effect of fermentation time and various color of sweet potato to the quality of sweet potato flour. The research was done on April until June 2015 in Basic Laboratory of Agricultural College of Dharma Wacana, while the proximate test for the flour of fermented sweet potato was done in Agricultural Product Technology Laboratory of State Polytechnic Lampung. The research design used in this study was Complete Group Random Design (RAKL) arranged factorially by three repetitions. The first factor is fermentation time (t) that has 3 levels: 5 days (t1), 7 days (t2), and 9 days (t3). The second factor is the color of sweet potato (w) that has 3 levels: white (w1), yellow (w2), and purple (w3). The finding result shows that the effect of fermentation time and various color of sweet potato have real impact towards the flour yield, ash content, color, and  flour smell as well as nutrient content of sweet potato such as water, protein, fat, crude fiber, and carbohydrate. Generally, there is no interaction except for the flour color and ash content.